Modifikasi Rancang Bangun Kondensasi Uap Air Laut untuk Mendapatkan Air Murni - Yuga, Ahmad Yudha; Tamrin, Tamrin; Warji, Warji; Kuncoro, Sapto (abe.fp.unila.ac.id, 2022)
Water is a natural resource that is needed for the necessities of life for many people, even by all living things on earth. Therefore, water resources must be protected so that they can still be used properly by humans and other living things. In human life always need water, so research is carried out. Modification of the design of the condensation device for the greenhouse model to purify seawater needs to be developed to obtain fresh water. The purpose of this study is to convert seawater using solar energy from the sun using the principle of the greenhouse effect. This research uses the method of designing, assembling, and testing the performance of the tool. The test results of this tool have been able to evaporate sea water in one day ranging from 708 ml - 924 ml, while the water that can be harvested in one day ranges from 190 ml - 300 ml. The energy efficiency obtained in this tool ranges from 7.92% - 9.31%, while the efficiency of the evaporation results from this tool is obtained from a value ranging from 26.98% - 32.46%. This tool has been able to change seawater into fresh water using the principle of the greenhouse effect but is still not able to work optimally. Keywords: Sea water, Fresh water, Greenhouse effect.